Entrapment neuropathies: a contemporary approach to pathophysiology, clinical assessment, and management - Annina B. Schmid; Joel Fundaun; Brigitte Tampin (PAIN Reports, 2020)
Abstract. Entrapment neuropathies such as carpal tunnel syndrome, radiculopathies, or radicular pain are the most common peripheral neuropathies and also the most common cause for neuropathic pain. Despite their high prevalence, they often remain challenging to diagnose and manage in a clinical setting. Summarising the evidence from both preclinical and clinical studies, this review provides an update on the aetiology and pathophysiology of entrapment neuropathies. Potential mechanisms are put in perspective with clinical findings. The contemporary assessment is discussed and diagnostic pitfalls highlighted. The evidence for the noninvasive and surgical management of common entrapment neuropathies is summarised and future areas of research are identified.